2020
DOI: 10.1093/cvr/cvaa012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic lineage tracing reveals poor angiogenic potential of cardiac endothelial cells

Abstract: Aims Cardiac ischaemia does not elicit an efficient angiogenic response. Indeed, lack of surgical revascularization upon myocardial infarction results in cardiomyocyte death, scarring, and loss of contractile function. Clinical trials aimed at inducing therapeutic revascularization through the delivery of pro-angiogenic molecules after cardiac ischaemia have invariably failed, suggesting that endothelial cells in the heart cannot mount an efficient angiogenic response. To understand why the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…4). These findings were recently supported by a genetic lineage tracing study showing that VEGFA overexpression in the (uninjured) myocardium was sensed by CECs, as demonstrated by apelin expression, however, in contrast to ECs of skeletal muscle, CECs failed to induce downstream angiogenesis 111 . Similarly, the angiogenic enhancer:LacZ constructs coud be ectopically activated by VEGFA injection in other adult tissues, and indeed were still active in remote regions of the MI heart.…”
Section: Molecular Mechanisms Of Neovascularisationmentioning
confidence: 75%
“…4). These findings were recently supported by a genetic lineage tracing study showing that VEGFA overexpression in the (uninjured) myocardium was sensed by CECs, as demonstrated by apelin expression, however, in contrast to ECs of skeletal muscle, CECs failed to induce downstream angiogenesis 111 . Similarly, the angiogenic enhancer:LacZ constructs coud be ectopically activated by VEGFA injection in other adult tissues, and indeed were still active in remote regions of the MI heart.…”
Section: Molecular Mechanisms Of Neovascularisationmentioning
confidence: 75%
“…This is because an excess of VEGF-B works merely by binding to the VEGFR-1 decoy receptor, thereby displacing the endogenous VEGF for induction of angiogenesis through the VEGFR-2-signaling pathway, which in turn promotes mild CMC growth through paracrine EC-CMC crosstalk 48 . It is important to note, that the therapeutic dosing window is much smaller for VEGF-A than for VEGF-B, because VEGF-A is poorly angiogenic in the heart 49 , and its side effects, such as vascular leakage and inflammation are greater, which thus far has compromised its use in the treatment of cardiovascular ischemic conditions 21,22,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the generation of new blood vessels with αSMApositive cells coverage in myocardial tissues has been recently reported, and αSMA-positive arterioles were discovered in newly formed vascular networks (26). αSMA-positive arterioles were also observed in skeletal muscles and heart tissues of mice with adeno-associated virus-mediated VEGF overexpression (27). The authors reported that VEGF-induced formation of new arterioles in the heart occurred to a lesser extent than in skeletal muscle.…”
Section: Discussionmentioning
confidence: 94%